2017
DOI: 10.4085/120146
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Education in Athletic Training

Abstract: Context: Clinical education is a foundational component of healthcare education by which students acquire, practice, and demonstrate competency in clinical proficiencies through classroom, laboratory, and clinical experiences. Currently, the most common practice of clinical education in athletic training is clinical integration. Objective: The purposes of this article are to describe how athletic training and similar health p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…12 Although how clinical education is delivered can be up to the athletic training program administrators, it has been viewed as an effective means for students to be ready for transition to autonomous practitioners. [33][34][35] Our participants, reported that time engaged in their clinical education experiences allowed them to acquire knowledge of the professional responsibility of athletic trainers as well as to be aware of the types of things they would be required to do as well as treat. Moreover, research suggests that exposure to the employment setting one is assuming can also facilitate a successful transition to clinical practice, as awareness can reduce the stress associated with the transition.…”
Section: Educational Mechanismsmentioning
confidence: 99%
“…12 Although how clinical education is delivered can be up to the athletic training program administrators, it has been viewed as an effective means for students to be ready for transition to autonomous practitioners. [33][34][35] Our participants, reported that time engaged in their clinical education experiences allowed them to acquire knowledge of the professional responsibility of athletic trainers as well as to be aware of the types of things they would be required to do as well as treat. Moreover, research suggests that exposure to the employment setting one is assuming can also facilitate a successful transition to clinical practice, as awareness can reduce the stress associated with the transition.…”
Section: Educational Mechanismsmentioning
confidence: 99%
“…Programs can opt to use clinical integration or clinical immersion models. 6,48 With the clinical immersion models, students are immersed full time into the clinical setting without taking classes concurrently or taking a few courses online. With this model, students are not limited to geographically convenient clinical sites, and programs can instead use clinical sites with effective preceptors who view the clinical experience as truly educational.…”
Section: Clinical Opportunities: Role Of the Preceptor Level Of Invomentioning
confidence: 99%
“…Athletic training programs could implement the clinical immersion model, in which athletic training students are immersed in clinical education full time, allowing them to experience all aspects of the ATs' role. 6,48 Another option would be to restructure clinical experiences to focus on completion of proficiencies instead of obtaining a certain number of hours. During the clinical experience, patient encounters could be tracked and evaluated to ensure athletic training students are implementing competencies during clinical education.…”
Section: Clinical Opportunities: Role Of the Preceptor Level Of Invomentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical education is important for the socialization of athletic training students (ATS) and is characterized by the integration of ATS into clinical practice through the supervision of a preceptor. 1 Researchers have demonstrated that ATS place a large value on the influence of the preceptor for mentorship and role modeling. 2 Clinical experiences can serve as a catalyst for smooth transition into the workforce.…”
Section: Introductionmentioning
confidence: 99%